Aprender em Piaget: o significado da inclusão a partir das possibilidades de desenvolvimento e aprendizagem de nossos alunos - Zaia, Lia Leme; Saravali, Eliane Giachetto [UNESP] (My University, 2011)
This article proposes a reflection on the relevance of Piaget’s work when it comes to inclusion. It presents the basic concepts of development and learning in the constructivist perspective. It also reflects upon the currently emphasized conceptual and practical aspects of school inclusion, which were already anticipated by Piaget.

Este artigo propõe uma reflexão sobre a atualidade da obra piagetiana quando o assunto é inclusão. Apresenta os conceitos básicos sobre o desenvolvimento e a aprendizagem na perspectiva construtivista. Reflete sobre aspectos conceituais e práticos da inclusão escolar enfatizados atualmente e já antecipados por Piaget.
Learning in Piaget: the meaning of inclusion from our students’ possibilities of development and learning